Biocompatible fluorescent carbon quantum dots prepared from beetroot extract for in vivo live imaging in C. elegans and BALB/c mice. Issue 20 (11th May 2018) - Singh, Vikram; Rawat, Kundan S.; Mishra, Shachi; Baghel, Tanvi; Fatima, Soobiya; John, Aijaz A.; Kalleti, Navodayam; Singh, Divya; Nazir, Aamir; Rath, Srikanta K.; Goel, Atul
Abstract : Luminescent carbon quantum dots (CQDs) prepared from aqueous beetroot extract were developed as unique fluorescent nanomaterials for in vivo live animal imaging applications. Abstract : Luminescent carbon quantum dots (CQDs) prepared from aqueous beetroot extract were developed as unique fluorescent nanomaterials for in vivo live animal imaging applications. Blue (B) and green (G) emitting environmentally benign CQDs (particle size of 5 nm and 8 nm, respectively) exhibited bright fluorescence in aqueous medium and were found to be biocompatible, photostable and non-toxic in animal models. The in vivo imaging and toxicity evaluation of both CQDs were performed for the first time in the Caenorhabditis elegans ( C. elegans ) model, which revealed consistent fluorescence in the gut tissues of the worms without exerting any sign of toxic effects on the nematodes. The in vivo bio-distribution of G-CQDs given by tail vein injection in live BALB/c mice showed optical signals in the lower abdominal regions, mainly in the intestine, and cleared from the body through faeces. The tremendous potential shown by these eco-friendly CQDs in the C. elegans and mice models advocates new hopes for greener CQD nanomaterials as diagnostic tools in the biomedical field.